Restrukturisasi Sistem Fraksi Di DPR RI Guna Mewujudkan Pembangunan Demokrasi - Patricia, Tiara; Gunawan, Chyntia; Yudhistira, Dhiwatsani (Lex Librum : Jurnal Ilmu Hukum, 2023)
Abstract In the Indonesian constitution, it is explained that the sovereignty of the Indonesian state is in the hands of the people as stated in Article 1 paragraph (2) of the 1945 Republic of Indonesia Constitution so all actions taken by the state must side with the interests of the people. Indonesia is a country that adheres to a democratic system, which means from the people to the people. Indonesia is a country of law so it has a logical consequence that every state action must have a clear legal basis. The DPR is a legislative institution that represents the interests of the people as explained in Article 20 paragraph (1) of the 1945 Republic of Indonesia Constitution states that: "The DPR holds the power to form laws." So the DPR has the authority to greatly influence the development of democracy and law in Indonesia. However, Article 82 paragraph (1) of Law Number 17 of 2014 concerning the MPR, DPR, DPD and DPRD states that: "Factions are groupings of members based on the configuration of political parties based on the results of general elections." So that the existence of factions in the DPR's organizational structure can result in deviations from the Indonesian constitution because in practice the factions in the DPR only care about their existence in parliament and try to maintain their power and defend the interests of their own party, so it is necessary to restructure the faction system in the DPR which eliminates factions in the DPR's organizational structure and restores them. to its initial function of realizing democratic development. Keywords: Restructuring, Development, Democracy, DPR RI Faction